2021
DOI: 10.1007/s12283-021-00346-1
|View full text |Cite
|
Sign up to set email alerts
|

Applying ubiquitous sensing to estimate perceived exertion based on cardiorespiratory features

Abstract: Reliable monitoring of one’s response to exercise intensity is imperative to effectively plan and manage training, but not always practical in impact sports settings. This study aimed to evaluate if an inexpensive mobile cardio-respiratory monitoring system can achieve similar performance to a metabolic cart in estimating rated perceived exertion. Eight adult men volunteered to perform treadmill tests under different conditions. Cardiorespiratory data were collected using a metabolic cart and an instrumented o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

5
1

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 54 publications
0
3
0
Order By: Relevance
“…One study (1/85, 1%) used a microphone embedded in a mouthguard to estimate the perceived exertion of athletes in running exercises. The study reported a normalised root-mean-squared error of 16.20% [ 106 ].…”
Section: Resultsmentioning
confidence: 99%
“…One study (1/85, 1%) used a microphone embedded in a mouthguard to estimate the perceived exertion of athletes in running exercises. The study reported a normalised root-mean-squared error of 16.20% [ 106 ].…”
Section: Resultsmentioning
confidence: 99%
“…The oral monitoring device, based on the device used in ref. [ 15 ], consisted of a flexible design that continuously measures several intra-oral signals (including temperature) at the same time. It was vacuum formed using ethylene-vinyl acetate (EVA).…”
Section: Methodsmentioning
confidence: 99%
“…The clips of continuous breathing were then pre-processed through a series of filters. A 4th order Butterworth band-pass filter of 100Hz-400Hz was applied forward and back on the data to get rid of low and high-frequency noises outside of the range of breathing [3]. Following that, the data were downsampled to 1600Hz.…”
Section: B Data Processingmentioning
confidence: 99%
“…It has been shown that breathing frequency, but not heart-rate, has a strong relationship to RPE [2]. Respiratory rate correlates well to physical exertion [3], and can potentially be used to monitor recovery from exertion better than heart rate [4], thus presenting a promising additional on-field physiological metric to help improve the health and well-being of athletes.…”
Section: Introductionmentioning
confidence: 99%